An unexpected complication of videothoracoscopic lobectomy: late RIMA bleeding - Ancın, Burcu; Uysal, Serkan; Dikmen, Erkan; Doğan, Rıza (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2022)
Videothoracoscopic (VATS) lobectomy, a minimally invasive technique, has been performed for approximately 20 years [1]. The advantages include improved patient satisfaction due to less surgical trauma, less postoperative pain, faster recovery, and less invasiveness compared to open surgical techniques [2]. Endoscopic vascular and parenchymal staplers are widely used for video-assisted thoracic surgery (VATS) and are mostly considered a safe technique [3]. In our case report, a patient, who underwent uniportal VATS lobectomy for lung adenocarcinoma and who was reoperated on due to the development of massive right internal mammary artery bleeding due to the intraoperative use of stapling, is presented.